Synthesis and characterization of self-organized TiO2 nanotubes grown on Ti-15Zr alloy surface to enhance cell response - Konatu, R. T. [UNESP]; Domingues, D. D. [UNESP]; Escada, A. L.A. [UNESP]; Chaves, J. A.M.; Netipanyj, M. F.D.; Nakazato, R. Z. [UNESP]; Popat, K. C.; Grandini, C. R. [UNESP]; Alves Claro, A. P.R. [UNESP] (My University, 2021)
In recent years, studies have been shown that the presence of TiO2 nanotubes on the titanium alloy surfaces could induce the enhancement of the cell adhesion on the titanium alloys surface. In the present study, the cell response of the surface of the Ti-15Zr alloy after TiO2 nanotubes growth (NTs) via anodic oxidation was evaluated. TiO2 NTs were obtained in organic electrolytes and analyzed after annealing using Scanning electron microscopy (SEM), X-ray diffraction (XRD), and Raman spectroscopy. The attachment and growth of adult human adipose-derived stem cells (ADSCs) were considered for 1 and 7 days for better annealing conditions (450°C). Besides, the influence of the TiO2 NTs growth on the corrosion resistance and Staphylococcus epidermidis bacterial adhesion was evaluated. Results indicated that a self-organized and homogeneous layer of TiO2 nanotubes was formed. XRD analysis and SEM micrographs confirmed that as-anodized, amorphous nanotubes crystallized into anatase phase at 450°C. According to electrochemical analysis, Ti-15Zr alloy exhibited better corrosion resistance compared to commercially pure titanium (cp Ti), but there was no significant difference in passivation capacity between samples evaluated before and after anodization. It was observed that an increase in cellular adhesion and no significant difference in bacterial proliferation occurred despite the presence of TiO2 nanotubes which changed the surface roughness.